Graphic Carbon Nitride-SilverPolyvinylpyrrolidone Nanocomposite Modified on a Glassy Carbon Electrode for Detection of Paracetamol - Mekgoe, N.; Mabuba, N.; Pillay, K. (Frontiers in Sensors, 2022)
In this study a nanocomposite of graphitic carbon nitride-silver polyvinylpyrrolidone (gCN-AgPVP) was fabricated for the electrochemical detection of paracetamol (PAR). The nanocomposite of gCN-AgPVP showed superior electrocatalytic ability for PAR detection since it is selectively adsorbed by electrostatic interactions of the nanocomposite of gCN-AgPVP. This selective adsorption is also facilitated by charge assisted interactions between the PAR and gCN-AgPVP surfaces. The stability of the GCE/gCN-AgPVP was characterised using cyclic voltammetry (CV) at potentials ranging from-0.2 to +0.7 V and a scan rate of 50mV/s. Square wave voltammetry (SQWV) was employed to characterise and detect PAR. The analysis was conducted on modified GCE/gCN-AgPVP in 0,1M phosphate buffer solution (PBS) and pH 6.1. GCE/gCN-AgPVP showed excellent performance in detecting PAR in the concentration range of 0.2 to 100 µM with a correlation coefficient of 0.9951 respectively. The calculated detection limit (LOD) was 0.079µM.